Benefits And Drawbacks Using Information And Communication Technology In English Teaching - Omila Odilovna Yuldasheva (Euro Asian Journal Publishing, 2024)
This article analyzes to discussesthe advantages and disadvantages of using technology in the classroom. The article ends with recommendations for future studies in education that highlight the importance of digital literacy for academic goals.
Keywords: digital literacy; benefits; drawbacks; ICT